Cortical progenitor biology: key features mediating proliferation versus differentiation. Issue 5 (27th June 2018) - Uzquiano, Ana; Gladwyn‐Ng, Ivan; Nguyen, Laurent; Reiner, Orly; Götz, Magdalena; Matsuzaki, Fumio; Francis, Fiona
Abstract: The cerebral cortex is a highly organized structure whose development depends on diverse progenitor cell types, namely apical radial glia, intermediate progenitors, and basal radial glia cells, which are responsible for the production of the correct neuronal output. In recent years, these progenitor cell types have been deeply studied, particularly basal radial glia and their role in cortical expansion and gyrification. We review here a broad series of factors that regulate progenitor behavior and daughter cell fate. We first describe the different neuronal progenitor types, emphasizing the differences between lissencephalic and gyrencephalic species. We then review key factors shown to influence progenitor proliferation versus differentiation, discussing their roles in progenitor dynamics, neuronal production, and potentially brain size and complexity. Although spindle orientation has been considered a critical factor for mode of division and daughter cell output, we discuss other features that are emerging as crucial for these processes such as organelle and cell cycle dynamics. Additionally, we highlight the importance of adhesion molecules and the polarity complex for correct cortical development. Finally, we briefly discuss studies assessing progenitor multipotency and its possible contribution to the production of specific neuronal populations. This review hence summarizes recent aspects of cortical progenitor cell biology, and pinpoints emerging features critical for their behavior. Abstract : In this review, we focus on the exquisite regulation between the different cortical neuronal progenitor types, namely apical radial glia, intermediate progenitors, and basal radial glia, the latter being characteristic of species with bigger and more complex brains, containing gyri and sulci. We review key progenitor features, recently described to influence transitions between them and to mediate proliferation versus differentiation toward a more committed state in the neuronal lineage. Although spindle orientation has been considered important to regulate daughter cell output, other features are also being revealed as crucial to determine cell fate, such as extracellular cues, and organelle and cell cycle dynamics. In addition, adhesion and polarity complex molecules are clearly critical to assure correct cortex development. This new review summarizes diverse and current aspects of neuronal progenitor cell biology, while pinpointing emerging features regulating key steps related to these important cell types.